1985
DOI: 10.1144/gsjgs.142.5.0747
|View full text |Cite
|
Sign up to set email alerts
|

Flow separation—a physical process for the concentration of heavy minerals within alluvial channels

Abstract: Flow separation is a common feature within alluvial channels that occurs at abrupt changes in the bed geometry. At a wide range of scales, it is a process that can exert considerable control over the segregation and deposition of heavy mineral grains. Fluid separation generates a region of high bed shear stress that can entrain heavy minerals, and a region of low velocity that is a preferred site for the deposition of denser particles. Significant concentrations of heavy minerals, sometimes up to eight times t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Additionally, the process of selective grain entrainment could be reproduced by the numerical simulations, which further helps to answer the second research question. At the beginning of the simulations, with well‐mixed beds, the light particles were more frequently entrained than heavy particles, consistent with the experimental findings reported by Komar () and Best & Brayshaw (). Consequently, the light particles were subsequently separated from the heavy particles.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the process of selective grain entrainment could be reproduced by the numerical simulations, which further helps to answer the second research question. At the beginning of the simulations, with well‐mixed beds, the light particles were more frequently entrained than heavy particles, consistent with the experimental findings reported by Komar () and Best & Brayshaw (). Consequently, the light particles were subsequently separated from the heavy particles.…”
Section: Discussionsupporting
confidence: 92%
“…Best (1987) showed that avalanche faces can develop on the upstream end of these scours (Fig. Best and Brayshaw 1985), with the emergent bar acting as an obstacle within the channel. This allows the scours to be filled laterally, 167 obliquely, or vertically by an avalanche deposit in a short period of time during channel switching or a flood event.…”
Section: Hollows (Element Ho)mentioning
confidence: 99%
“…They reason that this phenomenon is due to the main channel capturing more and more tributary inputs in a downstream direction, with the asynchronous timing of water and sediment contributions from upstream ephemeral tributaries producing distinct laminae at each successive confluence. Heavy minerals may also concentrate along scour surfaces and within the sediments of channel junctions, and these sites can be areas of significant heavy-mineral accumulations (Mosley and Schumm, 1977;Best and Brayshaw, 1985;Carling and Breakspear, 2006).…”
Section: Sedimentologymentioning
confidence: 99%